Maritime English Proficiency and Its Impact on Equipment Maintenance and Safety: A Study of Onboard Communication - Sudarmin, Wahyudi; Zulfah Fakhruddin; Besse Sri Widistari (Institut Agama Islam Negeri Parepare, 2025)
Effective communication is crucial for the safe and efficient operation of maritime vessels, where the proficiency in Maritime English plays a significant role. This study examines the relationship between Maritime English proficiency and its impact on equipment maintenance and safety onboard ships. Through a combination of surveys, interviews, and observational research conducted with maritime professionals, the study assesses how varying levels of English proficiency affect the clarity of communication related to equipment maintenance tasks, incident reporting, and safety protocols. Findings reveal that higher levels of proficiency in Maritime English are associated with improved accuracy in maintenance procedures, better understanding of safety instructions, and a reduction in communication-related errors. The study underscores the necessity for enhanced English language training programs for maritime personnel and suggests practical measures to improve communication practices on board. The results highlight the broader implications for maritime safety and operational efficiency, emphasizing the need for ongoing investment in language skills development within the maritime industry.